The lymphatic absorption of the retinoids - Nankervis, Richard (1992)
An understanding of the criteria governing lymphatic absorption of drugs from the gastrointestinal tract may lead to selective uptake of drugs via this route. Lymphatic absorption may have potential advantages over the portal absorption of drugs; first pass elimination may be avoided as the drug reaches the systemic circulation before it reaches the liver, the absorption of some poorly absorbed drugs may be improved and it may provide a means of targeting anticancer agents directly to the lymphatics.